HOW GENERATION Z VIEWS THE SOCIAL CAPITAL OF FEMALE CANDIDATES? - Rofieq, Ainur; Purwantini, Lucky; Fadil, Muhammad; Ekayana, Ega Danar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2024)
The implementation of the 2024 simultaneous elections has ended. Many male and female candidates, as well as running for executive and legislative positions have introduced themselves to the public. However, various surveys show that female candidates are still unpopular and have low electability, especially presidential candidates. Generation Z voters can be categorized as first-time voters. As a generation, they have different characteristics from previous generations. They were born during the development of internet technology, so they are very internet literate. Therefore, this study aims to find out Generation Z's views toward female candidates from the perspective of social capital. The research method uses a quantitative descriptive approach. Based on the answers of 55 students, it was shown that there was no significant difference between the perception of female candidates in terms of gender and type of voters. However, judging from the interaction of gender and type of voters, there is a significant difference between female and non-female first-time voters. There is a difference in the perception of female candidates compared to male and non-female first-time voters.